2021
DOI: 10.3390/antibiotics10030238
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Escherichia coli and Related Enterobacteriaceae and Examination of Their Phenotypic Antimicrobial Resistance Patterns: A Pilot Study at A Wildlife–Livestock Interface in Lusaka, Zambia

Abstract: A cross-sectional study was used to identify and assess prevalence and phenotypic antimicrobial resistance (AMR) profiles of Escherichia coli and other enterobacteria isolated from healthy wildlife and livestock cohabiting at a 10,000 acres game ranch near Lusaka, Zambia. Purposive sampling was used to select wildlife and livestock based on similarities in behavior, grazing habits and close interactions with humans. Isolates (n = 66) from fecal samples collected between April and August 2018 (n = 84) were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…These results are almost identical to the findings of Kelsey et al (2003), who found that 97% of E. coli isolates from surface water were resistant to one or two antibiotics, with only one isolate resistant to more than two antibiotics. Multidrug resistance (MDR) was detected in 18.8% of E. coli isolates from healthy wildlife and livestock by Kabali et al (2021) which corroborates present study. On the contrary, Adzitey, 2015 had only four isolates with MAR index less than 0.2 out of 45 isolates of E. coli.…”
Section: Resultssupporting
confidence: 90%
“…These results are almost identical to the findings of Kelsey et al (2003), who found that 97% of E. coli isolates from surface water were resistant to one or two antibiotics, with only one isolate resistant to more than two antibiotics. Multidrug resistance (MDR) was detected in 18.8% of E. coli isolates from healthy wildlife and livestock by Kabali et al (2021) which corroborates present study. On the contrary, Adzitey, 2015 had only four isolates with MAR index less than 0.2 out of 45 isolates of E. coli.…”
Section: Resultssupporting
confidence: 90%
“… 65 Besides, E. coli isolates from wildlife and livestock were highly resistant to ampicillin (27%), ceftazidime (14.3%), cefotaxime (9.5%) and kanamycin (9.5%). 66 In these animal species, a prevalence of 36.5% MDR was reported in broilers 63 % and 18.8% in wildlife. 66 However, the study of the prevalence and AMR profiles of E. coli isolated from laying hens in Zambia was not reported prior to this study.…”
Section: Introductionmentioning
confidence: 97%
“…In Zambia, antimicrobial-resistant E. coli have been isolated from humans, 61 , 62 broiler chickens, 63 , 64 dairy 65 and wildlife and livestock. 66 In broilers, E. coli , was observed to be resistant to tetracycline, ampicillin, cotrimoxazole and ciprofloxacin, whereas, in dairy, it was resistant to tetracycline, ampicillin, cotrimoxazole and ciprofloxacin. 65 Besides, E. coli isolates from wildlife and livestock were highly resistant to ampicillin (27%), ceftazidime (14.3%), cefotaxime (9.5%) and kanamycin (9.5%).…”
Section: Introductionmentioning
confidence: 99%
“…Many microorganisms have become resistant to commonly used antimicrobials in livestock production [17]. Escherichia coli is one of the highly antimicrobial-resistant pathogens in livestock [18][19][20][21][22]. Equally, antimicrobial-resistant Enterococcus and Salmonella have been reported in livestock production [16,19,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%